2018
DOI: 10.1155/2018/7676580
|View full text |Cite
|
Sign up to set email alerts
|

Primary Bone Marrow B-Cell Lymphoma Undetected by Multiple Imaging Modalities That Initially Presented with Hypercalcemia

Abstract: Purpose We report a rare case of severe hypercalcemia that was ultimately diagnosed as primary bone marrow diffuse large B-cell lymphoma (BCL). Case Report A 74-year-old male patient visited our hospital complaining of tenderness and swelling of the left knee caused by supracondylar fracture of the left distal femur. His initial blood tests showed a serum calcium level of 13.9 mg/dL, inorganic phosphorus of 4.34 mg/dL, and a serum creatinine level of 1.54 mg/dL. A serum assay of intact parathyroid hormone show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…There are several case reports that describe lymphomas presenting as severe, unexplained hypercalcemia [9-11, 24, 25]. Hong et al reported a case of DLBCL in a 72-year-old male who presented with worsening confusion and dehydration and who, like our case, was found to have severe hypercalcemia along with high plasma concentration of PTHrP.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…There are several case reports that describe lymphomas presenting as severe, unexplained hypercalcemia [9-11, 24, 25]. Hong et al reported a case of DLBCL in a 72-year-old male who presented with worsening confusion and dehydration and who, like our case, was found to have severe hypercalcemia along with high plasma concentration of PTHrP.…”
Section: Discussionmentioning
confidence: 50%
“…Hypercalcemia has been reported in up to 15% of NHL patients during their clinical course but is uncommon at diagnosis [8]. Hypercalcemia has been described as a rare presenting symptom of patients with DLBCL in several case reports [9-11]. Presently, there is no published case report in the literature of THRLBCL presenting as severe hypercalcemia.…”
Section: Introductionmentioning
confidence: 99%
“…There were 51 high-grade BCL cases, and among these 77% (48/62) were DLBCL and 5% (3/62) were left unclassifiable. 1,3,5-33 Meanwhile, there were 11 cases of low-grade BCL, and 11% (7/62) were FLs. 1,34,35 According to the character of our case, we focused more on the analysis of HGBL.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient only had a mild thrombocytopenia, whereas in most described cases a severe form of thrombocytopenia with anemia has been shown [ 13 ]. In addition, a hypercalcemia and hemophagocytic lymphohistiocytosis can also be a part of clinical presentation in patients with bone marrow lymphoma [ 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%